2017
DOI: 10.1016/j.amsu.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ocular tuberculosis in Hospital Universiti Sains Malaysia - A case series

Abstract: IntroductionOcular tuberculosis (TB) encompasses a broad spectrum of clinical manifestations affecting different structures of the eye. It is caused by Mycobacterium tuberculosis, a great ancient organism that induces various types of diseases and unfavorable outcomes if unrecognized and not well treated.PurposeTo report the clinical profile of 34 ocular TB cases observed during 6 years period in Hospital Universiti Sains Malaysia (HUSM).MethodA retrospective review of medical records from 34 patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
5
16
0
Order By: Relevance
“…In another study in Malaysia by Shahidatul-Adha M et al with 1 case of tubercular optic neuritis were found. 21 In our study we found that 10 cases (47.61%) had bilateral involvement. In study conducted by Agrawal R et al, most patients had bilateral involvement (58.8%).…”
Section: Discussionsupporting
confidence: 46%
“…In another study in Malaysia by Shahidatul-Adha M et al with 1 case of tubercular optic neuritis were found. 21 In our study we found that 10 cases (47.61%) had bilateral involvement. In study conducted by Agrawal R et al, most patients had bilateral involvement (58.8%).…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, the glaucoma observed in this study in 4 cats (6 eyes) was a likely sequel to mycobacterial uveitis. 11,22,45…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, multiple single-center studies highlighted the therapeutic role of ATT in patients diagnosed with TAU. 20,21,24,25,29,38,44,45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Based on overall scientific evidence and experience, uveitis specialists reached mostly moderate consensus for initiating ATT in recurrent TAU with any immunologic evidence of tuberculosis, along with radiologic signs suggestive of pulmonary tuberculosis infection, in both endemic and nonendemic regions when other possible causes have been ruled out. However, when it comes to the first episode of anterior uveitis, experts agreed to initiate ATT, regardless of endemicity, only when 2 immunologic and radiologic tests show positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supported the efficacy of ATT in patients with TIU and TPU. 20e24, 26,30,31,38,44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Particularly in patients with TPU, any immunologic evidence of tuberculosis, along with positive radiologic signs, supports the initiation of ATT, regardless of endemicity. However, when comparing results from endemic and nonendemic regions, data confirmed once again that in an endemic area, where the pretest probability of TBU is higher, experts are more likely to treat patients with an isolated PPD test showing positive results, despite negative IGRA results.…”
Section: Discussionmentioning
confidence: 99%